1994
DOI: 10.1086/646828
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a Pseudo-Outbreak of Orthopedic Infections Caused by Pseudomonas aeruginosa

Abstract: Pseudoepidemics due to common organisms are often difficult to detect, and delayed recognition can result in substantial morbidity. This outbreak investigation illustrates the potential for contamination of diluents in the microbiology laboratory and emphasizes the need for meticulous quality control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…To date, countless P. aeruginosa nosocomial outbreaks have been described that were caused by patient-topatient transmission, environmental sources, or contaminated medical devices (5,(8)(9)(10). P. aeruginosa also has been reported as a cause of pseudo-outbreaks due to the contamination of media used for clinical specimen collection, transport, or analysis (6,12,13).…”
mentioning
confidence: 99%
“…To date, countless P. aeruginosa nosocomial outbreaks have been described that were caused by patient-topatient transmission, environmental sources, or contaminated medical devices (5,(8)(9)(10). P. aeruginosa also has been reported as a cause of pseudo-outbreaks due to the contamination of media used for clinical specimen collection, transport, or analysis (6,12,13).…”
mentioning
confidence: 99%
“…Recently, several authors have reported the use of PCRribotyping (3,5,7,8,12,22,23) and PCR-restriction fragment length polymorphism (PCR-RFLP) analysis (20,21) for strain differentiation within various bacterial species. In this work, we evaluated the ability of these two techniques to distinguish between R. paucula strains and between strains belonging to other Ralstonia species (R. eutropha, R. pickettii, R. gilardii, and R. solanacearum).…”
mentioning
confidence: 99%